Manajemen Kelas Inklusi untuk Meningkatkan Kualitas Pembelajaran Anak Berkebutuhan Khusus di PAUD Pelita Hati Kramatjati Jakarta Timur - Deka Syahbari; Ricky Yoseptry; Anna Pebriani; Baini Baini; Dede Yatimah; Agus Sugiono (STKIP PGRI SITUBONDO, 2025)
Abstract: Children are one of the most beautiful gifts that Allah SWT entrusts to parents. However, not all children are born perfect, there are some children who experience obstacles /disorders in their growth and development. There are still many parties who still look down on the existence of Children with Special Needs, and their lack of knowledge about inclusive education. The research is based on the 1945 Constitution, Article 32 paragraph 1, which states that every citizen has the right to receive an education, and Law Number 20 of 2003, Article 32 paragraph (1) states that “Special education is education for students who have difficulty in following the learning process due to physical, emotional, mental, social disorders, and/or have the potential for intelligence and special talents.” Special education aims to develop the potential of students optimally according to their abilities. Therefore, good inclusive class management is needed that is able to accommodate the learning needs of ABK. The formulation of the research problem is how to plan, organize, implement, evaluate and follow up on inclusive classes at PAUD Pelita Hati Kramatjati, Kramtjati District, East Jakarta. This research is a qualitative research conducted at PAUD Pelita Hati Kramatjati, Kramtjati District, East Jakarta. The results of the study indicate the following: 1) Inclusive education management has been carried out which includes planning, organizing, implementing and evaluating the components: Student recruitment, infrastructure management, human resource management, inclusive learning, assessment and reporting, supporting programs,, relations with the community, 2) follow-up to the inclusion program has been carried out by the PAUD Pelita Hati Kramatjati education unit, Kramtjati District, East Jakarta. with the existence of inclusive education at the elementary, junior high and high school levels.